Efforts to Increase Family Resilience Among Street Vendors Post Covid-19: Qirā’ah Mubādalah Perspective - Rohani, Rohani; Lastfitriani, Hellen; Anggraini, Nia; Bte Salman, Nola Fibriyani (Universitas Islam Negeri Raden Intan Lampung, 2023)
Domestic Violence (KDRT) is still a serious problem faced by low-income families, especially in the post-Covid-19 pandemic era. Even though the pandemic has ended, the social and economic impact it has caused continues, especially among street vendors. This research aims to examine the role of family resilience in overcoming domestic violence among low-income families after the Covid-19 pandemic using qirā'ah mubādalah perspective. This research is qualitative research using a phenomenological study approach. Data was collected through in-depth interviews with low-income families who had experienced cases of domestic violence after the Covid-19 pandemic. The data that has been collected is analyzed to identify factors that influence the level of family resilience in dealing with domestic violence, as well as the possibility of implementing qirā’ah mubādalah as an alternative solution to prevent the emergence of Domestic Violence (KDRT).